COVID-19 vaccines are not associated with axonal injury in patients with multiple sclerosis - Sainz de la Maza, Susana; Rodero-Romero, Alexander; Monreal, Enric; Chico-García, Juan Luis; Villarrubia, Noelia; Rodríguez-Jorge, Fernando; Fernández-Velasco, José Ignacio; Sainz-Amo, Raquel; Costa-Frossard, Lucienne; Masjuan, Jaime; Villar, Luisa María (Frontiers in Immunology, 2024)
Objective: To evaluate the safety of COVID-19 vaccines in patients with multiple sclerosis (MS) by assessing their impact on serum neurofilament light chain (sNfL) levels as a marker of neuroaxonal damage.Methods: Single-center observational longitudinal study including patients with MS who consecutively received their initial vaccination against SARS-CoV-2 at Hospital Universitario Ramón y Cajal, following the first national immunization program in Spain. Serum samples were collected at baseline and after receiving the second dose of the vaccine. sNfL levels were quantified using the single molecule array (SIMOA) technique. Adverse events, including clinical or radiological reactivation of the disease, were recorded.Results: Fifty-two patients were included (median age, 39.7 years [range, 22.5-63.3]; 71.2% female). After SARS-CoV-2 vaccination, no increased inflammatory activity, either determined by the presence of relapses and/or new MRI lesions and/or high sNfL levels, was detected. Accordingly, there was no difference between median sNfL levels before and after vaccination (5.39 vs. 5.76 pg/ml, p=0.6). Despite this, when looking at baseline patient characteristics before vaccination, younger age associated with disease activity after vaccination (OR 0.87, 95% CI: 0.77-0.98, p=0.022). Larger studies are needed to validate these results.Conclusion: COVID-19 vaccines did not cause reactivation of disease at a clinical, radiological or molecular level, thus suggesting that they are safe in MS patients.